2019
DOI: 10.1049/iet-stg.2018.0146
|View full text |Cite
|
Sign up to set email alerts
|

Optimal DG integration and network reconfiguration in microgrid system with realistic time varying load model using hybrid optimisation

Abstract: The potential availability of renewable energy sources is unquestionable and the government is setting steep targets for renewable energy usage. Renewable-based DGs, reduce dependence on fossil fuels, mitigate global climate change, ensure energy security, and reduce emissions of CO 2 and other greenhouse gases. This study addresses microgrid system analysis with hybrid energy sources and reconfiguration simultaneously for efficient operation of the system. Microgrid zones are formulated categorically with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 55 publications
(138 reference statements)
0
28
0
Order By: Relevance
“…eir objective functions were to minimize voltage stability and power loss. Murty et al [24] suggested the hybrid method of the General Algebraic Modelling System and Gravitational Search Algorithm for DNR and ODGP problem. e objectives of this problem were to maximize annual cost savings and minimize power loss.…”
Section: Introductionmentioning
confidence: 99%
“…eir objective functions were to minimize voltage stability and power loss. Murty et al [24] suggested the hybrid method of the General Algebraic Modelling System and Gravitational Search Algorithm for DNR and ODGP problem. e objectives of this problem were to maximize annual cost savings and minimize power loss.…”
Section: Introductionmentioning
confidence: 99%
“…In [19], the authors have employed the CDE optimizer for the DGs' placement. In [20], the authors have proposed a mixture of GA-GSA for a DG incorporation. In [21], a mixed WIPSO-GSA is proposed to install two DGs along with capacitors in the above-mentioned test networks.…”
Section: Introductionmentioning
confidence: 99%
“…In [33], an ASFLA for the optimal allocation of three DGs is selected. In [34], a combined GSA-GAMS has been availed for the optimal deployment of three DGs in the distribution networks. Similarly, the authors in [35], have tested the QOCSOS algorithm to search for the optimal locations of three DGs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fossil fuel resource depletion and environmental interests have encouraged the integration of renewable distributed generator (DG) units (eg, wind and solar) in distribution networks. These units have offered several advantages such as total loss reduction, improved total system efficiency, voltage stability and voltage profile improvement, enhanced reliability, green‐house gas emission reduction and they have a significant impact on the power flow, continuity, short circuit level, and power quality . However, the inappropriate choice of locations and sizes of DGs in electric power systems has adverse effects on voltages profile, transmission losses, feeder loading, stability, and system reliability .…”
Section: Introductionmentioning
confidence: 99%